STRATEGI PENGEMBANGAN AGRO INDUSTRI GULA TUMBU DI KABUPATEN KUDUS - Karmiati Karmiati; Vitus Dwi Yunianto; Bambang W.H.E. Prasetiyono (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
Tumbu sugar has been known by Indonesian people as one of sweetening for foods and beverages that can be substitute of sugar. That is what a potential of tumbu sugar processing business need to be analyzed and the formulation of strategies in its development efforts. The purpose of this study were: 1) to analyze the condition of tumbu sugar processing business, covering aspects of production, financial aspects and marketing aspects; 2) formulate a viable alternative strategy applied; 3) determine the priority strategies in the development of agro-industrial processing of tumbu sugar in District Kudus. This research was descriptive quantitative survey approach. The research location is in district of Kudus covers three sub-districts (Sub-District Dawe, Sub-District Bae, and Sub-District Gebog). Subjects in this study include the main actors of tumbi sugar producers, traders, government agencies and academia. The collection of data through observation, interviews, questionnaires and FGD (Focus Group Discussion). Data analysis using using descriptive analysis, financial analysis and marketing analysis, SWOT analysis (Strength, Weakness, Opportunity, Threat) to formulate the steps of strategy and analysis AHP (Analytical Hierarchy Process) for the determination of strategic priorities in the development of tumbi sugar agroindustrial, with tools Expert Choice program.The results showed that the value analysis of the financial aspects of the R/C ratio is 1.88 ; B / C ratio is 0.88 and an IRR is 36 %. Analysis of the marketing aspects of the farmer's share values ​​obtained low of 75.8 % and the highest value of marketing efficiency of 17.49 % . SWOT analysis obtained tumbu sugar agro-industry position is in quadrant I. AHP analysis obtained by the alternative strategy of product development innovation and product diversification.Based on the Results of the research concluded that the production aspects of the tumbu sugar agro-industry businesses in Kudus regency still scale households by family labor management through a process that is still simple, but remains open investment opportunities with marketing channels already running efficiently. The alternative strategy that is feasible in the tumbu sugar agro-industry development in District Jepara is a S-O strategy that supports the aggressive growth by prioritizing the development of innovative products or product diversification.